Recent Progress on Colorimetric Sensor for Hg(II) Detection - Hakim, Muh. Supwatul; Hermayantiningsih, Dwi; Wahyuningsih Manurung, Tety; Ariefin, Mokhamat; Roil Bilad, Muhammad (Jurnal Sains Materi Indonesia, 2025)
Mercury (Hg) contamination presents significant effects on human health and the environmental, particularly caused by its bio-accumulative and neurotoxic properties. Effective detection of Hg(II) is essential for monitoring and mitigating its impact. Among various detection methods, colorimetric sensors have developed into a promising solution due to their affordability, simplicity, and real-time detection capabilities. This review summarizes recent advancements in colorimetric sensors for Hg(II) detection, focusing on innovative materials such as silver nanoparticles (AgNPs), gold nanoparticles (AuNPs), paper-based substrates, agarose biopolymers, and carbon dots (CDs). AuNPs and AgNPs are highlighted for their unique optical properties and sensitivity, enabling visible detection through surface plasmon resonance changes. Paper-based sensors offer portability and low-cost solutions, while agarose serves as a stable biopolymer matrix for immobilizing detection agents. CDs, with their tunable fluorescence properties and green synthesis potential, provide a biocompatible option for hybrid sensing systems. Despite significant progress, challenges such as stability, selectivity in complex matrices, and scalability of green synthesis remain. Future research should focus on integrating these sensors into portable platforms and enhancing their performance for field applications. This review underscores the critical role of innovative materials and sustainable techniques in advancing mercury detection technologies